Hardware and software: verification and testing : 11th International Haifa Verification Conference, HVC 2015, Haifa, Israel, November 17-19, 2015 : proceedings /: 11th International Haifa Verification Conference, HVC 2015, Haifa, Israel, November 17-19, 2015 : proceedings. (2015) - Unknown
No abstract available